The Social Dynamics of Khulʿ. The Experience of German Muslims - Jaraba, Mahmoud (Routledge Handbook of Islamic Ritual and Practice, 2022)
Ritual and practice are one of the most distinctive features of religion, and they are linked with its central beliefs. Islam is no exception here, and this Handbook covers many aspects of those beliefs and practices. It describes the variety of what takes place but mainly why, and what the implications of both the theory and practice have for our understanding of Islam. The book includes accounts of prayer, food, pilgrimage, mosques, and the various legal and doctrinal schools that exist within Islam, with the focus on how they influence practice. The volume is organized in terms of texts, groups, practices, places, and others. An attempt has been made to discuss the wide range of Muslim ritual and practice and provide a sound guide to this significant aspect of the religious life of one of the largest groups of believers in the world today. <